STUDI PERBANDINGAN MORFOLOGI DAN MOLEKULER Clinostomum complanatum (DIGENEA: CLINOSTOMIDAE) PADA IKAN AIR TAWAR DI RIAU DAN YOGYAKARTA - , Ir.Morina RIauwaty S, Dipl.Biol.M.P ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Clinostomiasis is one of diseases caused by digenea trematoda Clinostomum complanatum, known well as "yellow grubs". This is a zoonotic parasite and causes the "laryngo-pharyngitis", and death caused by asphyxia in humans. Clinostomum complanatum infection of freshwater fish in Indonesia causes high fish mortality and economic losses. The objectives of research were a) to identify and to compare the morphological and molecular characteristics of C. complanatum (Digenea: Clinostomidae) infecting freshwater fishes in Riau and Yogyakarta, and b) to find out their strain variation. Climbing perch (Trichogaster trichopterus) infected by Clinostomum sp. were caught from Sail River of Riau, while climbing gouramy (Anabas testudineus) caught from Kali Progo, Yogyakarta. Excysted Clinostomum sp. was found in the body cavity and and visceral organ, were aseptically taken using needle, preserved in 10% formalin and absolute ethanol solution. Morphological examination was done with Semichonâs acetocarmine staining, Scanning Electron Microscope (SEM). Molecular examination performed by Polymerase Chain Reaction (PCR) method consisting of extraction, amplification in the ITS region, PCR-RFLP, electrophoresis and sequencing. Data obtained from sequencing results were analysed by maximum parsimony and neighbour-joining method. Genetic distances were calculated using Kimura parameter model. Based on morphological observation and Scanning Electron Microscope (SEM) the worm from Riau was categorized as a new species, whereas worm from Yogyakarta was identified as Clinostomum complanatum. The PCR rDNA product of Clinostomum sp. at ITS region had a clear band of 1300 bp. Product of RFLP using PstI and AluI restriction enzyme showed different site among the five worms, however, the RsaI and HaeIII enzyme could not digest well. There was intraspecific variation in Clinostomum sp. metacercariae in Riau and Yogyakarta. Phylogenetic analysis showed that Clinostomum sp. from Yogyakarta identic to Clinostomum complanatum, whereas Clinostomum sp. from Riau were suspected as a new species (difference > 2%) which is included in one cluster with Clinostomum phalacrocorasis.